2003
DOI: 10.1097/00024720-200306000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Atlantoaxial Stabilization: Clinical Comparison of Posterior Cervical Wiring Technique With Transarticular Screw Fixation

Abstract: Symptomatic atlantoaxial instability requires atlantoaxial stabilization. In this study the authors compared clinical, radiographic, and cervical outcome questionnaire results in 67 such patients who underwent 71 separate procedures. Thirty-eight patients had traditional posterior C1-C2 cervical wiring and halo-vest immobilization (group 1), whereas 33 were alternatively managed with transarticular screw fixation without rigid external immobilization (group 2). Mean follow-up in group 1 was 53.2 months and mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
1
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 36 publications
0
56
1
1
Order By: Relevance
“…[28][29][30]51,55,84) Posterior atlantoaxial fixation has been a treatment of choice for type II and some type III odontoid fractures, the most common upper cervical spine fracture. 33,34,52,67) Spine surgeons from North America have favored a posterior surgical approach for fixation of type II and III odontoid fractures. 8,11,14,58,87) In contrast, surgeons from Europe and Japan frequently perform and prefer the anterior odontoid screw fixation technique.…”
Section: Traumaticmentioning
confidence: 99%
“…[28][29][30]51,55,84) Posterior atlantoaxial fixation has been a treatment of choice for type II and some type III odontoid fractures, the most common upper cervical spine fracture. 33,34,52,67) Spine surgeons from North America have favored a posterior surgical approach for fixation of type II and III odontoid fractures. 8,11,14,58,87) In contrast, surgeons from Europe and Japan frequently perform and prefer the anterior odontoid screw fixation technique.…”
Section: Traumaticmentioning
confidence: 99%
“…4,6,8 However, they had lower fusion rates, necessitates intact posterior vertebral components and postoperative immobilization. 6,16,23 Transpedicular screw fixation was first pioneered in 1964 by Leconte and followed by Borne et al for treatment of traumatic spondylolisthesis (hangman ' s fracture) of axis. 3,11 Trans pars interarticularis screw is a modification of Magerl C1-C2 transarticular screw, 13 which is a non segmental fixation technique between C1-C2 requiring perfect preinsertion alignment of C1-2 joint for its safe placement.…”
Section: 22122mentioning
confidence: 99%
“…Any venous bleeding was easily stopped using hemostatic agents and gentle packing. We modified Brooks quite often did not provide sufficient rigidity and as a result nonunions rates were high 6,[8][9][10] . More recently, studies on biomechanics of the atlantoaxial joint have demonstrated that its kinematics is indeed complex and there is intervertebral coupled motion at the C1-C2 joints 11 .…”
Section: B1: Lateral C-spine X-ray Demonstrating a Severe C1-c2 Sublmentioning
confidence: 99%
“…Although some may argue that the transarticular screws combined with a wiring technique provide an excellent three-point fixation technique 1,2,12,14 , the passage of sublaminar wires is not without hazards 10,17 . This might be especially true for those patients in which there is a non-reducible C1-C2 subluxation and/or reduced space available for the cord.…”
Section: B1: Lateral C-spine X-ray Demonstrating a Severe C1-c2 Sublmentioning
confidence: 99%
See 1 more Smart Citation